Perkembangan Riset Akuntansi Dan Keuangan Bidang Pasar Modal: Evaluasi dan Kajian Ulang - Sutrisno, Sutrisno (Jurnal TEMA, 2002)
Market based accounting and finance research has grown rapidly as shown with the increasing number of research publication and in¬creasingly high interest of the researchers in the area. The growth is significantly affected by application of some other disciplines as econo¬metrics, statistics, behavioral science, computer technology, and changes in financial reporting environment. Endogenous factors con¬tributing to growth acceleration is the influence of the academics ac¬counting and finance community, through the research publication, conference and symposium, journal editorial policies, and promotion policies at colleges and universities. The study analyzes the growth of market based accounting and finance research by examining the research publication, identify¬ing, and discussing the possibility of direction in accounting and fi¬nance research. The main objective is to offer competing hypothesis and explanations for the observed findings. This naturally leads to unresolved issues and directions for future research noted through out the review. The results of the study are expected to provide a mapping of understanding, and interrelationship among the research area, and the current issues. Finally the study expected that students in accounting and finance find the study useful, especially for deter¬mining the research topic and preparing themselves for successful careers in research. Key words: accounting, finance, capital market, mapping, research growth, and publication.